Trends of risk factors associated with childhood stunting and anaemia in Ghana: evidence from the Demographic Health Survey and Multiple Indicator Cluster Survey (2003-2017) - Christian Sewor; Rajeev Jayalakshmi (Cambridge University Press, 2024)
Abstract Objective: This study investigated the trend of effect estimates of the key risk factors of childhood stunting and anaemia between 2003 and 2017. Design: A secondary analysis of the Demographic Health Survey (DHS) and Multiple Indicator Cluster Survey (MICS) data for the Ghanaian population between 2003 and 2017. Associations of selected socio-demographic (child age and gender; maternal age and education), economic (household wealth), environmental, dietary (minimum dietary diversity and iodine use) and health system (place of delivery and vaccination) factors were explored using the Poisson regression model. Trend analysis was explored using a fitted linear regression line on a time series plot. Setting: Ghana Participants: Children under 5 years Results: The results showed a reduction in the prevalence of stunting and anaemia over the 15-year duration. These health outcomes were found to be negatively associated with a wide array of socio-demographic (child age and gender, maternal age and education, residency), economic (household wealth), dietary (iodised salt use) and health service (place of delivery and vaccination) factors; however, the most consistent statistically significant association was observed between child's age and belonging to the poor wealth quintile. Conclusion: In order to prevent these indicators of child malnutrition, key consideration must be given to the early developmental stages of life. Child health policies must focus on addressing the key contextual factors of child malnutrition.